The Effect of Training and Compensation on Nurse Performance Through Job Satisfaction as an Intervening Variable at R.A.A Tjokronegoro Hospital in Purworejo, Central Java - Dhiyaa Budi Utami; Trias Setiawati (UNIVERSITAS PAKUAN, 2024)
The title of this research is